1995
DOI: 10.1079/bjn19950150
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity, body composition and bone density in ballet dancers

Abstract: The main purpose of the present study was to examine factors that d e c t bone mineral density (BMD) in female ballet dancers. Training history, Ca intake, body composition, total body BMD (TBMD) and site-specific BMD, and bone mineral content were described in twenty-four female ballet dancers (mean age 22.6 (SD 4.5) years). Training history was determined by questionnaires, Ca intake by 7 d dietary record, BMD and bone mineral content by dual-energy X-ray absorptiometry (DXA), total body water by 'H dilution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
46
3
3

Year Published

1998
1998
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(55 citation statements)
references
References 39 publications
3
46
3
3
Order By: Relevance
“…Significant correlations were seen between different dietetic and anthropometric parameters and both the BMD and BMC for the different areas studied (Table 3). The association between low body weight and poorer bone mineralisation has been reported by several authors (Van Marken Lichtenbelt et al, 1995;Wynn & Wynn, 1995;Young et al, 1995). In agreement, the dancers showed the lowest bodyweights and poorest bone densities.…”
Section: Discussionsupporting
confidence: 70%
“…Significant correlations were seen between different dietetic and anthropometric parameters and both the BMD and BMC for the different areas studied (Table 3). The association between low body weight and poorer bone mineralisation has been reported by several authors (Van Marken Lichtenbelt et al, 1995;Wynn & Wynn, 1995;Young et al, 1995). In agreement, the dancers showed the lowest bodyweights and poorest bone densities.…”
Section: Discussionsupporting
confidence: 70%
“…Several cross-sectional studies have implied that regular weight-bearing exercise has beneficial effects on bone mass in premenopausal women [1,4,6,8,14]. Heinonen et al [6] reported that athletes -squash players, aerobic dancers, and speed skaters -have significantly higher weight-adjusted BMD values at the loaded sites than sedentary controls.…”
Section: Discussionmentioning
confidence: 99%
“…Van-Marken-Lichtenbelt et al [14] reported that mean total BMD of ballet dancers is significantly higher (6%) than that of a reference population. These high values 284 could be attributed to the high BMD of legs and pelvis, the weight-bearing sites of the dancer's body.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been several reports regarding BMD in ballet dancers. Lichtenbelt et al reported that the BMD in ballet dancers (n = 24) was significantly higher than that of a reference population [19]. On the other hand, Lucas reported that the BMD of ballet dancers (n = 15) was not significantly different from the control subjects [20].…”
Section: Discussionmentioning
confidence: 99%